2015
DOI: 10.1038/gt.2015.56
|View full text |Cite
|
Sign up to set email alerts
|

miR-16 rescues F508del-CFTR function in native cystic fibrosis epithelial cells

Abstract: Cystic fibrosis (CF) is due to mutations in the CFTR gene, which prevents correct folding, trafficking and function of the mutant cystic fibrosis transmembrane conductance regulator (CFTR) protein. The dysfunctional effect of CFTR mutations, principally the F508del-CFTR mutant, is further manifested by hypersecretion of the pro-inflammatory chemokine interleukin-8 into the airway lumen, which further contributes to morbidity and mortality. We have hypothesized that microRNA (miR)-based therapeutics could rescu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 31 publications
0
15
0
Order By: Relevance
“…Numerous miRNAs had altered expression between CF and non-CF bronchial epithelium, and some of the altered miRNAs were predicted to regulate CFTR. Various other published studies have examined the role of miRNAs in the direct or indirect control of wild type (wt) or mutant CFTR expression [41][42][43][45][46][47][48][49][50].…”
Section: Other Mechanisms Affecting Cftr Expression In Cfmentioning
confidence: 99%
“…Numerous miRNAs had altered expression between CF and non-CF bronchial epithelium, and some of the altered miRNAs were predicted to regulate CFTR. Various other published studies have examined the role of miRNAs in the direct or indirect control of wild type (wt) or mutant CFTR expression [41][42][43][45][46][47][48][49][50].…”
Section: Other Mechanisms Affecting Cftr Expression In Cfmentioning
confidence: 99%
“…Interestingly, miR-138 and SIN3A were both shown to control a subset of genes and pathways important for wild type and mutant CFTR biogenesis. Moreover, miR-16 was shown to rescue the trafficking defects of F508del CFTR, likely through suppression of Heat shock protein 90 (HSP90), a chaperone involved in protein-folding activity (Kumar et al, 2015). We recently characterized a novel microRNA, miR-1343, that represses the receptors for transforming growth factor beta (TGF-β), a cytokine involved in wound-healing responses.…”
Section: Cystic Fibrosismentioning
confidence: 99%
“…This has been observed by Amato et al who found that the CFTR polymorphism (rs10234329) enhances the affinity for miR-509-3p, a potential CFTR transcript modulator [ 64 ]. Moreover, miR-16 was discovered to restore the deltaF508 CFTR protein function by regulating the cAMP-activated chloride conductance and by reducing the IL-8 expression [ 65 ].…”
Section: Ncrna Studies In Cystic Fibrosismentioning
confidence: 99%